Global and Regional CH4 Emissions for 1995–2013 Derived From Atmospheric CH4, δ13C‐CH4, and δD‐CH4 Observations and a Chemical Transport Model. Issue 14 (23rd July 2020) - Fujita, Ryo; Morimoto, Shinji; Maksyutov, Shamil; Kim, Heon‐Sook; Arshinov, Mikhail; Brailsford, Gordon; Aoki, Shuji; Nakazawa, Takakiyo
Abstract: To better understand the current global CH4 budget, biogenic, fossil fuel, and biomass burning CH4 fluxes for the period 1995–2013 were inversely estimated from the observed mole fraction data of atmospheric CH4 using a three‐dimensional chemical transport model. Then, forward simulations of carbon and hydrogen isotope ratios of atmospheric CH4 (δ 13 C‐CH4 and δD‐CH4 ) were conducted using the inversion fluxes to evaluate the source proportion of the global total CH4 emission. Model‐simulated spatiotemporal variations of atmospheric CH4 reproduce the observational results well; however, the simulated δ 13 C‐CH4 and δD‐CH4 values significantly underestimate their observed values as a whole. This implies that the proportion of biogenic CH4 sources in the global CH4 emission, deduced by inverse modeling, is overestimated, although the proportion is fairly comparable with the medians of recent multiple CH4 inverse modeling. To reduce the disagreement between the observed and calculated isotope ratios, the CH4 fluxes of individual source categories were adjusted using our atmospheric δ 13 C‐CH4 and δD‐CH4 data observed at Arctic and Antarctic surface stations. The resultant global average biogenic, fossil fuel, and biomass burning CH4 fluxes over 2003–2012 are 346 ± 11, 162 ± 2, and 50 ± 2 TgCH4 year −1, respectively. It is also strongly suggested that the leveling‐off of atmospheric CH4 in the early 2000s and the renewed growth after 2006/2007 are, respectively, explainable by the decrease in biogenic and biomass burning CH4 emissions for 2000–2006 and the increase in biogenic CH4 emissions after that period. These emission changes mainly originate in the tropics. Key Points: Inverse modeling of atmospheric CH4 and forward simulations of its δ 13 C and δD are made to estimate surface CH4 emissions for 1995–2013 The forward simulations reveal that the proportion of biogenic CH4 in global emission, deduced by the inverse modeling, is overestimated The plateau and regrowth of atmospheric CH4 in the 2000s are closely related with biogenic and biomass burning CH4 emissions in the tropics